Perioperative Interventions to Reduce Chronic Postsurgical Pain - Carroll, Ian; Hah, Jennifer; Mackey, Sean; Ottestad, Einar; Kong, Jiang Ti; Lahidji, Sam; Tawfik, Vivianne; Younger, Jarred; Curtin, Catherine (Journal of Reconstructive Microsurgery, 2013)
Approximately 10% of patients following a variety of surgeries develop chronic postsurgical pain. Reducing chronic postoperative pain is especially important to reconstructive surgeons because common operations such as breast and limb reconstruction have even higher risk for developing chronic postsurgical pain. Animal studies of posttraumatic nerve injury pain demonstrate that there is a critical time frame before and immediately after nerve injury in which specific interventions can reduce the incidence and intensity of chronic neuropathic pain behaviors–so called “preventative analgesia.” In animal models, perineural local anesthetic, systemic intravenous local anesthetic, perineural clonidine, systemic gabapentin, systemic tricyclic antidepressants, and minocycline have each been shown to reduce pain behaviors days to weeks after treatment. The translation of this work to humans also suggests that brief perioperative interventions may protect patients from developing new chronic postsurgical pain. Recent clinical trial data show that there is an opportunity during the perioperative period to dramatically reduce the incidence and severity of chronic postsurgical pain. The surgeon, working with the anesthesiologist, has the ability to modify both early and chronic postoperative pain by implementing an evidence-based preventative analgesia plan.
Keywords: pain; neuropathic pain; preventative analgesia